2019
DOI: 10.4314/ejhs.v29i5.4
|View full text |Cite
|
Sign up to set email alerts
|

Perception on the Quality of Life, Communication and Life Satisfaction among Individuals with Parkison’s and Their Caregivers

Abstract: BackgroundSpeech impairment, which reduces Quality of Life (QOL), frequently occurs in individuals with Parkinson's disease (PD). As speaking is required for social interaction, speech impairment can reduce one's life satisfaction. Although QOL has been well-studied in individuals with PD, the QOL of their caregivers has seldom been investigated. This study compared the QOL of individuals with PD and their caregivers. The relationships between QOL, self-rated speech scale, and life satisfaction level were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Outcomes included the impact of PD on caregivers' sleep (Bartolomei et al, 2018), burden (Bartolomei et al, 2018; Kudlicka et al, 2013), daily routines (Hurt et al, 2018; Padovani et al, 2018), and QoL (Bartolomei et al, 2018; Shin & Tan, 2019). The amount and quality of support caregivers received (Dekawaty et al, 2019; Shin & Tan, 2019), cultural and spiritual meaning gained (Dekawaty et al, 2019), caregivers' compassion (Walga, 2019), and self-care efforts (Hurt et al, 2018) were reported. Financial implications for caregivers (Martinez-Martin et al, 2018) and the shortage of and cost of PD medications were described (Walga, 2019).…”
Section: Rock Steady Boxingmentioning
confidence: 99%
“…Outcomes included the impact of PD on caregivers' sleep (Bartolomei et al, 2018), burden (Bartolomei et al, 2018; Kudlicka et al, 2013), daily routines (Hurt et al, 2018; Padovani et al, 2018), and QoL (Bartolomei et al, 2018; Shin & Tan, 2019). The amount and quality of support caregivers received (Dekawaty et al, 2019; Shin & Tan, 2019), cultural and spiritual meaning gained (Dekawaty et al, 2019), caregivers' compassion (Walga, 2019), and self-care efforts (Hurt et al, 2018) were reported. Financial implications for caregivers (Martinez-Martin et al, 2018) and the shortage of and cost of PD medications were described (Walga, 2019).…”
Section: Rock Steady Boxingmentioning
confidence: 99%
“…Findings motivating this theme reported on overall caregiver QOL as measured by a QOL scale and caregiver satisfaction with life and support. Six articles reported on the relationship between this caregiver factor and PD QOL, with most articles ( n = 4) revealing a positive relationship 50,59‐64 . Two articles did not find significant associations between these variables 47,54 .…”
Section: Resultsmentioning
confidence: 95%
“…Six articles reported on the relationship between this caregiver factor and PD QOL, with most articles (n = 4) revealing a positive relationship. 50,[59][60][61][62][63][64] Two articles did not find significant associations between these variables. 47,54 Most articles (n = 4) relied on univariable analyses, however, one article that did not report a significant relationship between…”
Section: Quality Of Life and Satisfactionmentioning
confidence: 92%
“…Although a cutoff value is not set, which represents good or bad perception of QOL in PD patients , our results suggest a worse perception of QOL in the sample investigated in relation to the results found by Balasch et al(2017), that were generally good for most, but not all, of the PDQ -39, where they obtained 20% to 25% significance for items 33 and 25 of the PDQ-39, which were related to embarrassment of Brazilian Journal of Development, Curitiba, v.7, n.3, p. 32875-32890 mar 2021 patients in dreams or hallucinations public and distressing. Chu and Tan (2019), studying 20 individuals with Parkinson's disease, observed a significant moderate correlation between the Life Satisfaction Scale and the PDQ-39 scores, suggesting that life satisfaction could affect their quality of life.…”
Section: Discussionmentioning
confidence: 99%